On the central limit theorem in R^k. III - Bikelis, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. О центральной предельной теореме в R^k. III A. Bikelis. Apie centrinę ribinę teoremą erdvėje R^k. III